Bariery rozwoju i upowszechniania się nowoczesnych struktur organizacyjnych - Lichtarski, Janusz Marek (Barriers for development and spread of modern organizational structures, 2007)
The dynamism of organizational environment causes birth and development of many concepts of modem, organic organizational structures in the theory of management. The author tries to identify main barriers and limitations for development and spread of modern structural solutions in this article. The text is based on literature studies and author’s own experiences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 53-63